2010
DOI: 10.1007/s00403-010-1043-6
|View full text |Cite
|
Sign up to set email alerts
|

A minimally invasive human in vivo cutaneous wound model for the evaluation of innate skin reactivity and healing status

Abstract: Individual variability in skin reactivity and healing capacity after trauma are important clinical issues. The aims were to develop an in vivo, human wound model based on a standardised minimal skin injury and to demonstrate therapeutic effect of simple wound therapies in terms of morphological wound outcome with changes in skin blood perfusion as a quantified indicator of wound healing. In a series of experiments, wounds were induced on the normal forearm skin of volunteers using a blood collection lancet. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 49 publications
3
6
1
Order By: Relevance
“…Skin blood flow data agree with those in the literature of an inflammatory phase which peaks around 2–3 days post‐wounding, which was the same for both wound models 1. In another human wound model using a blood collection lancet, Varol and Anderson 18 however reported a much shorter inflammation peak (assessed by laser Doppler perfusion imaging) occurring only 24 hours after wounding and followed by a rapid decrease.…”
Section: Discussionsupporting
confidence: 88%
“…Skin blood flow data agree with those in the literature of an inflammatory phase which peaks around 2–3 days post‐wounding, which was the same for both wound models 1. In another human wound model using a blood collection lancet, Varol and Anderson 18 however reported a much shorter inflammation peak (assessed by laser Doppler perfusion imaging) occurring only 24 hours after wounding and followed by a rapid decrease.…”
Section: Discussionsupporting
confidence: 88%
“…It then subsided over time and had returned close to baseline levels after 14 days. The results, when we used TiVi instead of laser Doppler-based technologies, are in concordance with earlier studies [102]. However, no inflammatory response could be detected between the interventions, suggesting that exogenous intradermal HA does not affect the inflammatory response as measured by TiVi.…”
Section: Paper IIIsupporting
confidence: 80%
“…This model allows standardized, highly reproducible, multiple skin wounds to be studied for re-epithelialization and dermal regeneration following different interventions [101]. Further on, we have developed an earlier described minimally invasive in vivo wound model [102]. In this process, we produced standardized deep dermal wounds with blood collection lancets and analyzed the wounds by tissue viability imaging, histology and proteomics.…”
Section: Wound Models Used In This Thesismentioning
confidence: 99%
“…This is proportional to the speed and concentration of red blood cells in the tissue [ 20 ]. This device has been used in an acute human wound model and demonstrated that this technique is useful for small acute wounds [ 21 ].…”
Section: Methodsmentioning
confidence: 99%